2005
DOI: 10.1111/j.1440-1746.2004.03398.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B vaccine boosters: Is there a clinical need in high endemicity populations?

Abstract: The Steering Committee for the Prevention and Control of Infectious Diseases in Asia recently conducted a survey of primary-care physicians in Asia, which revealed that many physicians administer boosters in their clinical practice and that there is considerable variation and uncertainty among physicians regarding this practice. This paper serves as a response to physicians' uncertainties by reviewing the literature regarding the administration of hepatitis B vaccine boosters in high endemicity areas and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Moreover, there is growing evidence that the antibody titre declines with age, especially after the age of 15 years 12 , 24 27 , 47 . The latest guidelines of the Steering Committee for the Prevention and Control of Infectious Diseases in Asia recommend a booster dose of HBV vaccine: (i) 10 to 15 years after primary vaccination in Asian populations where the virus is highly endemic and where it is not feasible to monitor antibody levels; (ii) in immunocompromised patients when the antibody titre falls to below10 mIU/mL; and (iii) in health-care workers 48 . A booster dose was also suggested for individuals who have a poor response to the vaccine and for high-risk adolescents 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is growing evidence that the antibody titre declines with age, especially after the age of 15 years 12 , 24 27 , 47 . The latest guidelines of the Steering Committee for the Prevention and Control of Infectious Diseases in Asia recommend a booster dose of HBV vaccine: (i) 10 to 15 years after primary vaccination in Asian populations where the virus is highly endemic and where it is not feasible to monitor antibody levels; (ii) in immunocompromised patients when the antibody titre falls to below10 mIU/mL; and (iii) in health-care workers 48 . A booster dose was also suggested for individuals who have a poor response to the vaccine and for high-risk adolescents 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, international public health authorities did not recommend a booster for immune competent people after primary immunization because of the robust anamnestic response to HBV in most people for many years after priming, even when antibodies were undetectable upon exposure. [20][21][22][23] Nevertheless, some studies in Taiwan have revealed the absence of an anamnestic anti-HBs response Table 2. anti-HBs response after HB vaccination given at month 0, 1, and 6 among participants seronegative for HBsag, anti-HBs, and anti-HBc at baseline in approximately 25% adolescents after one booster dose.…”
Section: Discussionmentioning
confidence: 99%
“…In highrisk groups, anti-HBs monitoring is significant and a booster dose of vaccine should be given if anti-HBs are lower than 10 mIU/ml. 17 In Beijing, local governments or medical facilities have granted HBV immunization of health care workers. 18 However, in most areas in China, the expenses of HBV vaccine immunization of high-risk populations should be covered by personal payment.…”
Section: Immunization Strategies For Children and High Risk Populatiomentioning
confidence: 99%